SUKSES KEPEMIMPINAN DALAM PANDANGAN AL-QUR'AN - Suwarno, Suwarno (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
Abstract Every nation and country wants progress and prosperity, as well as Indonesia, which is currently the most exposed country in the Southeast Asia region with a total of 311,176 positive cases as of October 6, 2020, Indonesia as a country with a majority Muslim population with the Al-Quran as the holy book it is very necessary and required to deepen the noble values taught by the Koran, especially for leaders and prospective leaders. The results of this study indicate that successful leadership based on the Qur'an consists in learning the values of worship taught by the Koran which consists of prayer that teaches discipline, fasting that teaches the spirit of trust, zakat which teaches caring, and hajj that teaches totality and in sacrifice.